1999
DOI: 10.1046/j.1365-2141.1999.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aml1‐eto Chimaeric Transcription Factor in Acute Myeloid Leukaemia: Biology and Clinical Significance

Abstract: Acute myeloid leukaemia (AML) is a heterogenous disease, with individual cases showing variability in clinical presentation, blast cell morphology, therapeutic response and long-term prognosis. This heterogeneity extends to the molecular genetic lesions underlying the pathogenesis of AML. Although nonrandom clonal chromosomal aberrations are present in the majority of cases, each abnormality affects only a limited subset of cases. Nonetheless, recent studies have demonstrated that several chromosomal rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(131 citation statements)
references
References 131 publications
(155 reference statements)
1
126
0
4
Order By: Relevance
“…It has been shown that AML1-ETO protein can regulate the transcription of many genes important for hematopoiesis including the M-CSF receptor, the G-CSF receptor and BCL2 (all upregulated) as well as GM-CSF, TCR subunits (a, b and d), NP3 and MDR1 (all downregulated). 25 In addition, the AML1-ETO chimeric protein leads to dysplastic granulopoiesis in a knockin mice model. 26 Dysplastic granulopoiesis, a high density of G-CSF and M-CSF receptors and a low density of MDR1 have been noted in leukemic blasts with t(8;21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that AML1-ETO protein can regulate the transcription of many genes important for hematopoiesis including the M-CSF receptor, the G-CSF receptor and BCL2 (all upregulated) as well as GM-CSF, TCR subunits (a, b and d), NP3 and MDR1 (all downregulated). 25 In addition, the AML1-ETO chimeric protein leads to dysplastic granulopoiesis in a knockin mice model. 26 Dysplastic granulopoiesis, a high density of G-CSF and M-CSF receptors and a low density of MDR1 have been noted in leukemic blasts with t(8;21).…”
Section: Discussionmentioning
confidence: 99%
“…Core-binding factor (CBF) acute myeloid leukaemia (AML) exhibit gene rearrangements which involve genes encoding CBF subunits, such as AML1 (CBFa2) or CBFb. In particular, the translocation t(8;21; q22;q22), which leads to gene repression via the formation of the AML1/ETO chimaeric gene, may represent a paradigm for a molecular mechanism of leukaemogenesis (Downing, 1999). In contrast to AML1, which recruits the transcriptional co-activators p300 and CBP endowed with intrinsic histone acetyl transferases (HAT) activity, AML1/ETO recruits, via NCoR/Sin3A, the histone deacetylase 1 (HDAC1), which drives the transcriptional repression of AML1-controlled genes (Ogawa et al, 1993;Ogryzko et al, 1996;Gelmetti et al, 1998;Kitabayashi et al, 1998;Wang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…52,53 It has been shown to be important in transcriptional activation and repression and it has also been implicated in DNA replication, although evidence suggests that the critical target genes have yet to be identified. 54 The ETO gene is located on chromosome 8q22 and encodes the mammalian homologue of the Drosophila protein Nervy. 55 Identification of other ETO family members involved in translocations with AML1 suggests that ETO sequences are critical for the transforming activity of these fusion proteins.…”
Section: Wt1mentioning
confidence: 99%
“…55 Identification of other ETO family members involved in translocations with AML1 suggests that ETO sequences are critical for the transforming activity of these fusion proteins. 54 Experimental evidence involving interactions between ETO and the nuclear co-repressors N-CoR and Sin3A, which can recruit an active histone deacetylase, suggests that it is likely to function as a regulator of transcription. 56-58 ETO can form homodimers and heterodimers and it is likely that these multisubunit complexes function in transcriptional regulation and the formation of different heterodimers may lead to functional differences in the activity of these complexes.…”
Section: Wt1mentioning
confidence: 99%
See 1 more Smart Citation